A Case of Laparoscopic-Assisted Percutaneous Endoscopic Gastrostomy (LAPEG) for Gastric Volvulus. (3rd December 2019) - Ueda, Shuhei; Orita, Hajime; Ito, Tomoaki; Tokuda, Satoshi; Sakuraba, Shunsuke; Kushida, Tomoyuki; Sakurada, Mutsumi; Maekawa, Hiroshi; Sato, Koichi
Abstract : Background . Percutaneous endoscopic gastrostomy (PEG) is the standard modality for long-term enteral nutrition for patients with dysphagia. Compared with open gastrostomy, though PEG is an extremely safe procedure with fewer complications, there are severe cases due to anatomical features. For these cases, laparoscopic-assisted percutaneous endoscopic gastrostomy (LAPEG) is the optimal method. Case Presentation . A 52-year-old man had a disturbance in swallowing because of cerebral infarction. We attempted PEG under gastrointestinal fiberscope (GIF) and colon ﬁberscope inspection; however, the procedure was unsuccessful because it was impossible to move the transverse colon downward. We therefore attempted LAPEG to observe the stomach and other organs. Under laparoscopic observation, we diagnosed gastric volvulus, classified as the organo-axial type. For this reason, inserting the tube through the skin was very difficult. We easily corrected the gastric volvulus by using laparoscopic forceps and were finally able to place the PEG tube safely. Discussion . Gastric volvulus is rare in clinical practice. The treatment of gastric volvulus depends on whether mucosal ischemia is present. Endoscopic reduction of gastric volvulus is effective for many patients. Surgical treatment should be considered for patients with gastric volvulus that frequently recurs. In our patient, completely inserting the GIF was impossible; therefore, we could not correctly diagnose gastric volvulus. Laparoscopy-assisted PEG is a useful and safe technique for placing a gastrostomy tube in patients presenting with anatomical difficulties. Moreover, in our patient, gastropexy was performed with PEG. Therefore, LAPEG may be used to prevent the recurrence of gastric volvulus. Gastropexy is a useful option in LAPEG. Conclusions . Laparoscopy has the advantage of allowing a direct inspection of the stomach while gastrostomy is performed and may reveal complications to PEG insertion. Furthermore, in our patient, gastropexy was performed with PEG.